Penegakan Hukum Kepabeanan dalam Rangka Penanganan Tindak Pidana Penyelundupan Barang Ekspor dan Impor di Indonesia - Ika Ariani Kartini; Bayu Setiawan (Universitas Muhammadiyah Purwokerto, 2019)
Customs crimes in Indonesia are still relatively high, both in frequency and in the value of state losses. During 2005 and the current year 2006, the number of arrests resulting from surveillance in the customs area was 164 and 118, respectively, with state losses of Rp. 11.6 billion and Rp. 20.2 billion, respectively. Meanwhile, the catch data from the marine patrols of the Directorate General of Customs and Excise for 2005 and 2006 were 128 and 89 arrests, respectively, with an estimated state loss of Rp. 10.9 billion and Rp. 4.8 billion. For details and details, see tables 1,2,3 and 4. It can be assumed that customs crimes that are unknown or not caught are much bigger. Based on Law No. 10 of 1995 concerning Customs, Presidential Decree No. 109 of 2001 concerning Organizational Units and Duties of Echelon I Departments which have been amended several times, most recently by Presidential Decree No.23/2004 and Minister of Finance Decree no. 302/KMK.01/2004, the duties of the Directorate General of Customs and Excise (DJBC) are: Service and Supervision of the traffic of goods entering and leaving the territory of the Republic of Indonesia. And Collection of State Revenue in the form of Import Duty (and Excise). The service function is the duty of DGCE to ensure the smooth flow of goods and documents efficiently and effectively, without a high cost economy, encouraging increased trade and competitiveness. The function of supervision is especially the supervision of the traffic of goods in the context of protecting the interests of the community from attempts to import goods that can damage health and disturb the public, harm consumers, and endanger state security. Thus, it is clear how big and heavy the duties and responsibilities of DJBC are, particularly in preventing and taking firm action against customs violations and criminal acts that can cause state losses in a broad sense, namely financial, security, health, trade and domestic industry/investment disturbances, and trust. society against the government.Keywords: Crime, Customs, Export, Import.